我国首批回收的四块南极陨石类型的确定 - 陈晶; 刘小汉; 琚宜太; 徐军; 阎允杰 (岩石学报, 2001)
中国第 15次南极考察队于 1999年元月在格罗夫山实施首次考察时回收了四块陨石 ,填补了我国南极陨石回收的空白。根据国际陨石协会命名委员会新回收陨石的命名原则 ,这些陨石已分别命名为 GRV980 0 1,GRV980 0 2 ,GRV980 0 3和GRV980 0 4。根据初步岩石、矿物以及全岩化学分析 ,这四块陨石分别属于石质球粒陨石 (GRV980 0 1) ,L5型球粒陨石(GRV980 0 2 ) ,H5型球粒陨石 (GRV980 0 4)和极细粒八面体铁陨石 (GRV980 0 3)。 Four Antarctic meteorites have been collected for the first time from the Grove Mountains of East Antarctica, during the 15th Chinese National Antarctic Research Expedition (15th CHINARE) in 1998 similar to 1944 austral season. According to the new nomenclature principles of The Nomenclature Committee of International Meteorite Association, these four meteorites are respectively nominated as GRV98001. CRV98002, GRV98003 and GRV9004. After primary studies of petrology, mineralogy and chemical analysis, the classification of these meteorites is as follows: GRV98001, CRV98002 and GRV98004 belong to the ordinary chondrite. GRV98002 attributes to the L5 group and the GRV98004 attributes to the HS group; while GRV98003 attributes to the extreme fine grain octahedron iron meteorite. http://gateway.webofknowledge.com/gateway/Gateway.cgi?GWVersion=2&SrcApp=PARTNER_APP&SrcAuth=LinksAMR&KeyUT=WOS:000168457600016&DestLinkType=FullRecord&DestApp=ALL_WOS&UsrCustomerID=8e1609b174ce4e31116a60747a720701 SCI(E) 中文核心期刊要目总览(PKU) 中国科学引文数据库(CSCD) 5 02 314-320 17